The importance of the instructor being a writing model and setting up the writing environment / Mazli Shahurain (Universiti Teknologi MARA, Sarawak, 2004)
In learning to speak, to read and to write, the student observes the instructor as a genuine user of the language. The student is invited to participate because he/she has a need for and the interest in learning to write which is a skill in the learning of a language. The writer believes that when student is not learning, it is because the demonstrations are not given or are inadequate and are not seen as meaningful to the learner. This idea is significant at the tertiary level where many students are turned off. Based on research and classroom experience, being a model in the classroom environment will enhance the learning process.